Algal-bacterial consortium promotes carbon sink formation in saline environment - Wenhui Gu; Songcui Wu; Xuehua Liu; Lijun Wang; Xulei Wang; Qi Qiu; Guangce Wang (Journal of Advanced Research, 2024)
Introduction: The level of atmospheric CO2 has continuously been increasing and the resulting greenhouse effects are receiving attention globally. Carbon removal from the atmosphere occurs naturally in various ecosystems. Among them, saline environments contribute significantly to the global carbon cycle. Carbonate deposits in the sediments of salt lakes are omnipresent, and the biological effects, especially driven by halophilic microalgae and bacteria, on carbonate formation remain to be elucidated. Objectives: The present study aims to characterize the carbonates formed in saline environments and demonstrate the mechanisms underlying biological-driven CO2 removal via microalgal-bacterial consortium. Methods: The carbonates naturally formed in saline environments were collected and analyzed. Two saline representative organisms, the photosynthetic microalga Dunaliella salina and its mutualistic halophilic bacteria Nesterenkonia sp. were isolated from the inhabiting saline environment and co-cultivated to study their biological effects on carbonates precipitation and isotopic composition. During this process, electrochemical parameters and Ca2+ flux, and expression of genes related to CaCO3 formation were analyzed. Genome sequencing and metagenomic analysis were conducted to provide molecular evidence. Results: The results showed that natural saline sediments are enriched with CaCO3 and enrichment of genes related to photosynthesis and ureolysis. The co-cultivation stimulated 54.54% increase in CaCO3 precipitation and significantly promoted the absorption of external CO2 by 49.63%. A pH gradient was formed between the bacteria and algae culture, creating 150.22 mV of electronic potential, which might promote Ca2+ movement toward D. salina cells. Based on the results of lab-scale induction and 13C analysis, a theoretical calculation indicates a non-negligible amount of 0.16 and 2.3 Tg C/year carbon sequestration in China and global saline lakes, respectively. Conclusion: The combined effects of these two typical representative species have contributed to the carbon sequestration in saline environments, by promoting Ca2+ influx and increase of pH via microalgal and bacterial metabolic processes.